MENGENAL HAK ASASI MANUSIA: KONSEP DASAR, SEJARAH, DAN KARAKTERISTIKNYA DALAM ANALISIS TEORITIS ATAS KASUS PELANGGARAN HAK DI KOTA KUPANG - Oswaldus Rinaldi; Novia Srinestava Sari; Stevania Gladis Ola; Fadil Masud; Jelita Makdarenci Laitera; Fadil Mas’ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Human Rights (HAM) are a set of fundamental rights inherent in every human being from birth as a gift from God Almighty and cannot be revoked by anyone. This study aims to explain the basic concepts, history, and characteristics of human rights and examine their implementation in the local context in Kupang City, East Nusa Tenggara. This study uses a descriptive qualitative approach with a normative-empirical approach, through literature review, policy document analysis, and secondary data from reports from the National Commission on Human Rights (Komnas HAM), BPS, SUAKA, and SIMFONI-PPA. The results show that normatively, Indonesia has a comprehensive human rights legal framework through the 1945 Constitution, Law No. 39 of 1999, and various derivative regulations. However, implementation at the regional level still faces significant challenges, particularly in terms of the gap between legal norms and practice in the field. Two cases that have come to the fore in Kupang City are the issue of statelessness among Afghan refugees and gender discrimination against female workers in the public sector. These two phenomena reflect the lack of synchronization between national policies and the capacity of regional implementers. This research emphasizes the importance of strengthening local context-based human rights protection through synergy between local governments, human rights institutions, and civil society to realize more substantive justice and humanity in Indonesia.